A Causation Analysis of Chinese Subway Construction Accidents Based on Fault Tree Analysis-Bayesian Network - Qie, Zijun; Yan, Huijiao (Frontiers in Psychology, 2022)
Clarifying the causes of subway construction accidents has an important impact on reducing the probability of accidents and protecting workers' lives and public property to a greater extent. 138 investigation records of subway construction accidents from 2000 to 2020 were collected in this paper. Based on a systemic analysis of 29 well-known accident causation models and the formative process of the subway construction accidents, we extracted the causative factors of subway construction accidents from the collected records. Further, a causation analysis index system of subway accidents was proposed based on fault tree analysis (FTA), where we regard subway construction accidents as the top event and the five dimensions as first-level intermediate events, i.e. human, equipment, environment, management, and safety culture. Moreover, 17 causative factors were considered to be related to the severity of subway construction accidents. It is found that human factors are prone to be critical to high-risk accidents. Finally, A Bayesian network(BN) was formed to explore the causative factors of high-risk subway construction accidents. Based on the combined application of FTA and BN, this paper discusses the complex influence factors and their action routes to unsafe accidents in subway construction sites, and makes efforts to correspond safety decision basis for the management of China subway construction.